Universal Design Principles for Older People and Older People with Disabilities During the COVID-19 Pandemic - Chrzanowska, Olga (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
This study aims to investigate the existing situation of the COVID-19 pandemic from an architectural and urban perspective. The problem analyzed in the study was whether and how universal design could be a useful tool in creating a meaningful response to social repercussions caused by COVID-19. Of the various issues faced today, this study focused on solving the issue of isolation and reducing infections in elderly and elders with disabilities by introducing architectural and spatial modifications. This research showed that all seven universal design principles when introduced at the architectural and urban levels can solve various issues that elderly people face today during the pandemic. It is executed through administrative and institutional push toward better accessibility and inclusion in a build environment that also works for general public interest.